Numerical investigation of flow boiling characteristics for helical cruciform fuel based on Euler-Euler method - Mei, Zhongkai; Wen, Qinglong (Annals of nuclear energy, 2026)
•The flow boiling characteristics of helical cruciform fuel is investigated.•The accuracy of numerical method is verified and validated by experimental data.•The effect of key variables on flow boiling characteristics is examined.•The distribution of thermal-hydraulics parameters is analyzed. Helical cruciform fuel (HCF) is a kind of novel fuel element design with a petal-shaped cross section and its blades are twisted along the axial direction to form a spiral structure. This structure endows the new fuel with advantages such as self-supporting characteristics, a large surface area-to-volume ratio, high power density, and strong turbulent mixing properties, which has been received worldwide attention so far. Although the single-phase heat transfer and mixing characteristics of helical cruciform fuel have been extensively investigated, little attention is paid to their flow boiling characteristics, which hinders the optimization design and practical application of HCF. Therefore, this work employs the Euler-Euler method to investigate the boiling characteristics of HCF, where the case of a single rod and 19-rod configuration is considered. The numerical model is carefully verified and validated, while the effect of subcooling degree and inlet temperature on boiling characteristics is examined. The results reveal that the vapor phase tends to be collected on the elbow for the single rod case, which is mainly connected to the flow pattern. In terms of 19-rod configuration, the presence of hexagonal arrangement could result in liquid residual in the blade-to-blade region between two neighbor rods even if the heat flux is sufficiently high, which is connected to the special structure of HCF and the intermixing of bulk fluid from various rods. The onset of boiling crisis is influenced by the spatial distribution of heat flux. Due to the presence of transverse mixing in 19-rod configuration, the effect of subcooling degree seems to be impaired and the boiling crisis is mainly subject to the magnitude of heat flux.